Creative Approach in Teaching the Chapter of Metals Working - Kenjayev Ravshanjon Qodirjon o`g`li (Genius Journals, 2022)
This article talks about the special features of the science of technology, attracting students to the world of spiritual and material culture on the basis of science, the types of students and the development of their individual characteristics.
Keywords: Industrial-technological locomotive; three groups of students; perseverance steel plate; saw blade; skills